Austerity, rationing and inequity: trends in children's and young peoples' services expenditure in England between 2010 and 2015. Issue 3 (4th May 2018) - Webb, Calum J. R.; Bywaters, Paul
ABSTRACT: This article investigates local authority (LA) trends in expenditure on Children's and Young Peoples' services in England between 2010 and 2015, a period of government characterised by measures of fiscal austerity. We draw on a rationing framework to contextualise the levels and trends in expenditure under observation. The article analyses trends in various groupings of expenditure, using a latent growth modelling approach to identify significant trajectories in spending across LAs with different deprivation tertile membership. We find that although some kinds of children's and young peoples' services expenditure have been largely maintained during this period, preventive family support and early intervention services (such as Sure Start Children's centres) have seen substantial reductions in expenditure, in contrast to the dominant narrative that children's services have been protected. LAs in the most deprived tertile have faced the greatest cuts, mirroring other research findings on the distribution of austerity measures.